IMPLEMENTASI ALAT PEMANTAUAN AKTIVITAS DAN PELACAKAN LOKASI JATUH (E-CARE) UNTUK LANSIA DI DAERAH CIKUTRA KOTA BANDUNG - Istiqomah,; Susanti, Hesty; Mukhtar, Husneni; Cahyadi, Willy Anugrah; Nugroho, Bambang Setia; Setiyadi, Suto; Afrinaldi, Nicola Akmal; Husnul, Nadia; Ardian, Fikri (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2022)
Indonesia has a percentage of an elderly population of as much as 9.03%, so it can be stated that Indonesia is a country with an old structure. This makes Indonesia pay attention to the health, activity, and productivity of the elderly. Changes in physical condition can affect the activities of the elderly significantly and increase the risk of falling. Therefore, a monitoring tool for elderly activities and location points for elderly falls was developed called e-care for the elderly. E-care Elderly is designed to be able to monitor the position of the elderly via GPS and detect if the elderly have fallen. This tool is connected to the application installed on the smartphone. In addition, this elderly E-care is equipped with a camera that can monitor the situation around the elderly. This service will be given to 10 elderly in Cikutra Village, Cibeunying Kidul District, Bandung City. There will be several preparations, implementation, and assistance activities for E-care for the Elderly. According to a survey of respondents who took part in this community service, more than 80% felt the tool had a performance that followed the needs, and 100% thought it was appropriate and very suitable for this activity with the goals and conditions of the community and it was hoped that the continuity of this activity. The survey results illustrate that the community understands all community service activities and how to use and benefit from E-Care tools. --- Indonesia memiliki persentase penduduk lansia sebanyak 9,03%, sehingga dapat dinyatakan indonesia merupakan negara berstruktur tua. Hal tersebut membuat Indonesia harus memperhatikan kesehatan, keaktifan, dan produktivitas dari lansia. Perubahan kondisi fisik dapat mempengaruhi aktivitas lansia terutama dan menambah resiko jatuh. Oleh karena itu dikembakan alat pemantau aktivitas lansia dan titik lokasi jatuh lansia yang dimamakan e-care lansia. E-care Lansia dirancang agar dapat memantau posisi lansia melalui GPS dan mendeteksi jika lansia terjatuh. Alat ini terhubung ke aplikasi yang terpasang pada telepon pintar. Selain itu, E-care lansia ini dilengkapi dengan kamera yang dapat memantau keadaan di sekitar lansia. Pada abdimas ini akan diberikan kepada 10 lansia di Kelurahan Cikutra, Kecamatan Cibeunying Kidul, Kota Bandung. Akan ada beberapa kegiatan persiapan, pengimplementasian dan pendampingan penggunaan E-care Lansia. Menurut survei responden yang mengikuti kegiatan abdimas lebih dari 80 % merasa alat memiliki kinerja yang sesuai dengan kebutuhan dan 100 % merasa sesuai dan sangat sesuai kegiatan ini dengan tujuan dan kebutuhan masyarakat dan diharapkan keberlangsungan kegiatan ini. Dari hasil survei tersebut juga bisa menggambarkan bahwa masyarakat sasar paham tentang seluruh kegiatan abdimas dan paham cara penggunaan dan manfaat dari alat E-Care.